S. N. Chernikov and the development of infinite group theory - Dixon, M.R.; Kirichenko, V.V.; Kurdachenko, L.A.; Otal, J.; Semko, N.N.; Shemetkov, L.A.; Subbotin, I.Ya. (Algebra and Discrete Mathematics, 2012)
In this survey, the authors want to show the development and continuation of some studies, in which S.N.Chernikov stood as the main originator and to demonstrate clearly the extent of influence exerted by the ideas and results of S.N.Chernikov on the modern theory of infinite groups.